Consideration of Parents in Choosing Islamic Schools in the Digital Era - Rokhman, Mauhibur; Usman, Fadly; Usman, Fatimah; Kassim, Azman Bin Haji; Muslihun, Muslihun (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
In the digital era, formal education is not only about learning at school but also about learning and education outside of school. This condition has more or less directly affected the consideration of parents in choosing a school, especially in the digital era. This research is conducted using quantitative and qualitative analysis methods. The quantitative method is performed by analyzing the potential of the schools chosen by parents, while the qualitative method is to find out the opinions of parents in more depth in choosing schools for their children. TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) analysis is performed which involves three experts in assessing good schools in the digital era. Three types of schools are used as research objects such as Islamic Boarding Schools, Public Schools, and Subsidized Schools. Some interesting findings related to considerations of parents in choosing a school are related to religious education for their children, access to education, and also the reason for the relatively expensive cost of Islamic-based schools. Therefore, parents tend to choose non-boarding public schools.